Factors Influencing Poor Implementation of Community Led Total Sanitation in Kajiado County, Kenya - Simbe, Juliana Yunia; Agoi, Lusiola Musa (European Journal of Applied Sciences, 2025)
The purpose of the study was to investigate the factors influencing poor implementation of CLTS in Magadi Ward, Kajiado County. Specifically, the study wanted to identify the socio-cultural factors influencing the poor implementation of CLTS, assess the accessibility of households to latrines, determine the latrine coverage and find out the community’s attitude, practice and knowledge on sanitation. A cross sectional descriptive study was adopted. Magadi was divided into four strata, each stratum represented its villages. The first household head to be interviewed was picked at random from the household register provided by the village headmen. Systematic random sampling was used to determine the number of villages and households to be interviewed. Data was collected by use of questionnaire and observation checklists. This was done by face to face interviewing of the respondents by trained CHVs. Qualitative data was processed through manual cleaning of the questionnaires by counter checking for completeness and then coded for easy entry. SPSS version 22.0 was used and descriptive findings presented in form of tables and pie charts. The study results revealed that 33% of the respondents had fully implemented CLTS while 67% strongly disagreed that OD caused diarrheal diseases and eye infections. Socio-cultural factors such as the community’s attitudes, practices and knowledge, low-latrine coverage and inaccessibility of households to latrines are the results of failure to proper implementation of CLTS. The study further revealed that 58% of respondents were not educated and 40% thought that CLTS is not necessary because of their nomadic lifestyle. The study findings concluded that the poor implementation of CLTS was caused by low knowledge levels and negative attitudes due to lack of education, poverty and nomadic lifestyle of the community.